Strawberry plant growth enhancement: Effects of artificial light and methyl jasmonate-salicylic acid treatments on physiology and metabolism - M. Adrian; Roedhy Poerwanto; Eiichi Inoue; Deden Derajat Matra (Heliyon)
Strawberries, known for their antioxidant properties, exhibit changes in physiology and metabolite profiles based on cultivation techniques. In Indonesia, strawberries are typically grown in highland regions, but climate change has necessitated adjustments in cultivation practices to enhance production and quality. This study investigates the adaptation of strawberry plants in lowland environments using light-emitting diodes (LEDs) and the exogenous application of methyl jasmonate (MeJA) and methyl salicylic acid (MeSA). A randomized block design was used with two factors: LED light types and MeJA–MeSA treatments. While the treatments did not significantly affect shoot growth (initially 1.5–2 cm, increasing 3–5 times by day 3), chlorophyll content, or fruit sugar levels, notable effects were observed in leaf glucose accumulation. The control group showed a fivefold increase (0.55 μg ml−1), while LED-hormone treatments resulted in a 27–64 % lower increase (0.20–0.40 μg ml−1). Fructose levels followed a similar pattern, and malic acid content was highest in the MeJA treatment (5.76 mg ml−1), with MeSA treatments also enhancing malic acid (5.91 mg ml−1). The secondary metabolite analysis, conducted using GC-MS and LC-MS, identified key defense-related compounds, including terpenoids, saturated fats, alkaloids, and amino acid derivatives, which play a role in the plant's defense mechanisms. These findings highlight the potential of LED lighting and hormone applications to modulate strawberry physiology and suggest further research into their role in plant stress responses.